Agricultural applications of starch nanoparticles: A scoping review - Gardella Caceres, Bryam Joao; Pareja Achahui, María de los Ángeles; Poma de la Cruz, Paulo César; Yactayo Audante, Angela Jimena; Martínez Molina, Giovanna Madeleyne; Rodriguez Carrillo, Sol (LACCEI, 2025)
In the highland regions, agriculture faces challenges due to factors such as irregular rainfall, temperature fluctuations, and soil erosion, which negatively impact the efficiency of conventionally applied fertilizers and pesticides. This study aims to explore the use of starch nanoparticles (SNPs) as an innovative solution in agriculture, specifically to improve the controlled release of nutrients and pesticides and reduce the ecological impact of inputs. A systematic review was conducted using the PRISMA methodology, where 226 articles were identified, and 9 studies were selected according to inclusion and exclusion criteria. The most reported method for nanoparticle preparation was nanoprecipitation, which allows the production of SNPs with controlled sizes that can encapsulate bioactive substances. Among the relevant results, it was highlighted that SNPs not only improve the efficiency of releasing active compounds such as fatty acids, urea, and phenolic compounds, but also provide greater stability and reduce volatilization. In conclusion, SNPs offer great potential to optimize the use of agricultural resources, providing an ecological and effective alternative for the controlled release of fertilizers and pesticides, which contributes to sustainability and improves agricultural performance in fragile areas.